Informative Advertising and Attitudes Towards Advertising - Cheung, Fanny; Guo, Guoqing; Leung, Wing-Fai (International Journal of Asian Business and Management, 2023)
An Infotainment advertisement is a type of TV advertisement which begins with providing knowledge to the audience and the sponsor’s name is shown only at the end of the advertisement. One question is that whether Infotainment advertisements are effective compared with advertisements focusing on own product information. Self-referencing is a reason that infotainments may have more positive attitudes toward the advertisement and thus the product. We operated 2x2x2 experiments, 2 products (facial masks vs card debt consolidation loans) 2 media (TV vs print) and 2 types of advertisements (i.e. Infotainment ad vs self-product-focused ad). The results suggest that the Infotainment TV ads do have positive effects on the audience’s attitudes toward the advertisement and product as well as purchase intention. However, the effects are not significant for print ads. The results may provide managerial implication on creating advertisements